Involvement of CREB3L1 in erythropoiesis induced by JAK2 exon 12 mutation - Okuda, Maho; Araki, Marito; De Marchi, Federico; Morishita, Soji; Imai, Misa; Fukada, Hanaka; Ando, Miki; Komatsu, Norio (Experimental hematology, 2024)
•CREB3L1 expression in RBCs discriminates JAK2 exon12 and V617F mutations.•CREB3L1 is required for the erythrocytosis associated with EPOR hyperactivation.•CREB3L1 may be a potential therapeutic target for MPN. [Display omitted] CREB3L1, a gene encoding the endoplasmic reticulum stress transducer, is specifically overexpressed in platelet RNA from patients with myeloproliferative neoplasms (MPNs). However, the pathophysiological roles of CREB3L1 overexpression remain unclear. In the present study, we aimed to study CREB3L1 messenger RNA (mRNA) expression in the red blood cells (RBCs) of patients with MPN and its role in erythrocytosis. Elevated expression of CREB3L1 was exclusively observed in the RBCs of patients with polycythemia vera (PV) harboring JAK2 exon 12 mutations, but not in those harboring JAK2 V617F mutation or control subjects. In erythropoiesis, CREB3L1 expression was sharply induced in erythroblasts of bone marrow cells collected from patients with JAK2 exon 12 mutation. This was also evident when erythropoiesis was induced in vitro using hematopoietic stem and progenitor cells (HSPCs) with JAK2 exon 12 mutation. Interestingly, overexpression of CREB3L1 in RBCs was observed in patients with reactive erythrocytosis whose serum erythropoietin (EPO) levels exceeded 100 mIU/mL. Elevated CREB3L1 expression was also observed in the erythroblasts of a patient with acute erythroid leukemia. EPO-dependent induction of CREB3L1 was evident in erythroblasts differentiated from HSPCs in vitro, regardless of driver mutation status or MPN pathogenesis. These data strongly suggest that CREB3L1 overexpression in RBCs is associated with hyperactivation of the EPO receptor and its downstream molecule, JAK2. Short hairpin RNA (shRNA) knockdown of CREB3L1 expression in HSPCs blocked erythroblast formation in vitro. These results suggest that CREB3L1 is required for erythropoiesis in the presence of JAK2 exon 12 mutation or high level of EPO, possibly by antagonizing cellular stress.